IMMUNOPHENOTYPIC CHARACTERISTICS AND TREATMENT OUTCOME OF T-ACUTE LYMPHOBLASTIC LEUKEMIA IN ADULTS; AN IRAQI CENTER EXPERIENCE - Abdulsalam Al-Ani; Alaadin Sahham Naji; Luma Essa Hamodi; Alaa Fadhil Alwan (Hematology, Transfusion and Cell Therapy)
Objective: About 25% of Acute Lymphoblastic Leukemia (ALL) express T-cell antigens which being considered a predictive of high-risk group. This study was conducted to find out the immunophenotypic characteristics of T-cell Acute Lymphoblastic Leukemia (T-ALL) in young and adult Iraqi patients. Also, to determine the association of treatment outcome with the immunophenotype and the treatment regimen used. Methodology: The study was conducted using the laboratory data of the Central Flowcytometry Department at Baghdad Medical City between 7 January 2019 and 3 May 2020. The immunophenotypic records revealed 35 young and adult patients (age of 14-year or older) with T-ALL. The patients were classified into early (immature) T-cell Precursor (ETP) and Mature T-cell Precursor (MTP). Correlation of the patients’ outcome according to age, gender, and immunophenotypic expressions with the type of therapy used were evaluated. Results: Thirty-five patients were diagnosed with T-ALL with a mean age of 28.1±12.3, and 74.3% were males. The stratification of patients according to the stage of leukemic T-cells maturation showed more frequent mature phenotype (cortical and medullary) than the immature (68.6% vs. 31.4%). The MTP markers expression showed a statistically significant higher rate in patients aged < 20-year (p = 0.03) or male (p = 0.01). Most patients received hyperCVAD 26 (74.3%) protocol, and UKALL was administered in the remaining (25.7%). Remission was achieved in 82.9%, while 11.4% failed to respond and 8.7% died during induction. Remission was maintained in 54.3% with 5-months of median follow-up, and relapse was found in 11.4%. The Overall Survival (OAS) at one year was 55%, with a mean survival of 13.8+1.7 months without an association with the type of therapy, subtype of T-cell, and myeloid antigenic expression. Despite a higher remission rate and lower death rate among UKALL group compared to HyperCVAD, the difference is non-significant (p = 0.81). The better response of MTP compared to ETP lineage was the only significant value with the outcome (p = 0.045). Conclusion: T-ALL is more commonly encountered in males. Remission was maintained in more than half of the patients with a better response and survival of the patients with MTP than those with the ETP subtype. The outcome was not affected by age, gender, or the treatment protocol.